A case of cuboid bone stress fracture in a senior high school rugby athlete - Tetsuo Hagino; Satoshi Ochiai; Yoshiyuki Watanabe; Shinya Senga; Yoshihiro Takayama; Hirotaka Haro (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2014)
We report a case of cuboid bone stress fracture in a 17-year-old rugby athlete. Cuboid bone stress fractures are rare in athletes. When an athlete with no history of trauma presents with pain on the lateral side of the foot and no abnormality on plain radiograph, cuboid bone stress fracture should be suspected and magnetic resonance imaging should be conducted.